2009
DOI: 10.1192/bjp.bp.108.051193
|View full text |Cite
|
Sign up to set email alerts
|

Why do antidepressants take so long to work? A cognitive neuropsychological model of antidepressant drug action

Abstract: Antidepressants may work in a manner consistent with cognitive theories of depression. Antidepressants do not act as direct mood enhancers but rather change the relative balance of positive to negative emotional processing, providing a platform for subsequent cognitive and psychological reconsolidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
436
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 470 publications
(470 citation statements)
references
References 46 publications
28
436
5
1
Order By: Relevance
“…insomnia) are prone to improve or worsen early in treatment as a consequence of side effects of the antidepressant, and hence will confound the assessment of early improvement. There is also some evidence that certain depressive symptoms may improve earlier and to a greater extent than other core symptoms [11,15,29]. Further research into new clinical metrics, possessing greater item sensitivity and specificity for detection of these early effects of antidepressant therapy, is required.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…insomnia) are prone to improve or worsen early in treatment as a consequence of side effects of the antidepressant, and hence will confound the assessment of early improvement. There is also some evidence that certain depressive symptoms may improve earlier and to a greater extent than other core symptoms [11,15,29]. Further research into new clinical metrics, possessing greater item sensitivity and specificity for detection of these early effects of antidepressant therapy, is required.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…8 In this model of depression, adult Wistar rats were socially deprived for a period of 15 days. Rats were housed singly in cages (38cm×26cm×20cm) without any visual or auditory contact with their normally housed counter parts for 15 days.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…140,141 Moreover, a number of studies have shown that changes in cognitive factors are not specific to CBT interventions [e.g. also being seen in patients receiving pharmacotherapy, 141,142 with some attributing such non-specific effects as being a consequence (rather than cause) of treatment 143 ].…”
Section: Introductionmentioning
confidence: 99%